Surgery of Larynx and Trachea - Remacle, Marc.; Eckel, Hans Edmund; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Written by internationally recognized opinion leaders of the field, this comprehensive textbook covers all the subspecialities of laryngology, from phonosurgery to cancer. Each surgical procedure is explained and well illustrated in a step-by-step manner. Moreover, different surgical methods such as endoscopic versus open surgery and the use of cold instrument versus laser are evaluated so that the reader receives guidance for the use of these complimentary methods.
Physiology of Voice Production -- Assessment of Voice and Respiratory Function -- Fundamentals of Laryngeal Surgery: Approaches, Instrumentation, and Basic Microlaryngoscopic Techniques -- Endolaryngeal Phonosurgery -- Microphonosurgery Using Cold Instruments -- Laser-Assisted Microphonosurgery -- Laryngeal Framework Surgery -- Laryngeal Surgery in Children -- Surgery for Benign Tumors of the Adult Larynx -- Laryngotracheal Blunt Trauma -- Glottic Airway Stenosis -- Subglottic and Tracheal Stenosis -- Tracheotomy -- Scarred Larynx -- Synechia of the Anterior Commissure -- Treatment Options for Laryngeal and Hypopharyngeal Cancer -- Endoscopic Approach -- Open Partial Resection for Malignant Glottic Tumors -- Surgery for Laryngeal and Hypopharyngeal Cancer -- Total Laryngectomy -- Voice Restoration -- Neurolaryngology -- Swallowing Disorders -- Nerve Reconstruction -- Helping Drugs -- Preoperative and Postoperative Speech Therapy.
Keywords: Medicine; Otorhinolaryngology; Head -- Surgery; Surgery; Endoscopic surgery; Medicine & Public Health; Otorhinolaryngology; Plastic Surgery; Head and Neck Surgery; Surgery; Minimally Invasive Surgery